Globalization, statist political economy, and unsuccessful education reform in South Korea, 1993-2003. - Kim, Ki Su (Education Policy Analysis Archives, 2005)
This article examines the relationship between globalization and national education reforms, especially those of educational systems. Instead of exploring the much debated issues of how globalization affects national educational systems and how the nations react by what kinds of systemic education reform, however, it focuses on what such a method often leaves out, viz., the internal conditions of a nation that facilitates or hampers reform efforts. Taking South Korea as an example, it explores that country's unique national context which restricts and even inhibits education reforms. Especially noted here is the established "statist" political economy in education. In the paper's analysis, although South Korea's statist political economy has made a substantial contribution to economic and educational development, it is now considered increasingly unviable as globalization progresses. Nevertheless, the internal conditions, resultant from the previous statist policies, set limits on policy makers' efforts to alter the existing educational system. The analysis suggests that a fuller assessment of globalization's impact upon national educational systems or their reforms requires a perspective which is broad enough to encompass not only the concepts and/or theories of globalization and nation states but also the power relations and ideological setup of individual nations.